Hubungan Tingkat Pengetahuan Dengan Tingkat Kecemasan Terhadap Covid-19 Pada Remaja Di SMA Advent Balikpapan - Gheralyn Regina Suwandi; Evelin Malinti (Malahayati Nursing Journal, 2020)
ABSTRACT : THE RELATIONSHIP BETWEEN LEVELS OF KNOWLEDGE AND LEVELS OF ANXIETY TOWARD COVID-19 AMONG ADOLESCENTS AT BALIKPAPAN ADVENTIST HIGH SCHOOL  Introduction: coronavirus Disease (Covid-19) that appear in Indonesia since the beginning of March 2020 has become a serious condition  to all age groups, including teenager. Teenager is called  age of transition, when biological and psychological development occurs. Covid-19 can affect the psychological development of adolescents, causing anxiety that can not be controlled. One of the factors that influence anxiety is knowledge.Purpose: the purpose of this  paper was to know the relationship between knowledge levels with anxiety levels in adolescents on the Covid-19 pandemic.Method: the study utilized a descriptive analytic with total sampling design. Respondents in this paper were all students of XII class in Balikpapan Adventist Senior High School totaling 60 people. Data collection using knowledge questionnaire adopted from the WHO surveyand  Hamilton Anxiety Rating Scale (HARS) questionnaire.Result: there were 9 respondents (15%) with standard knowledge felt mild anxiety, 33 respondents (55%) with good knowledge felt mild anxiety, 4 respondents (6.6%) with standard knowledge felt moderate anxiety, 9 respondents (15%) with good knowledge felt moderate anxiety, 1 respondent (1.7%) with standard knowledge felt severe anxiety, 4 respondents (6.7%) with good knowledge felt severe anxiety. The results of the chi-square test obtained p-value of 0.135 α (0,05).Conclusion: There is no relationship between the level of knowledge and the level of anxiety in adolescents at Balikpapan Adventist High School.   Keywords : adolescents; anxiety; covid-19; knowledge          INTISARI : HUBUNGAN TINGKAT PENGETAHUAN DENGAN TINGKAT KECEMASAN TERHADAP COVID-19 PADA REMAJA DI SMA ADVENT BALIKPAPAN Latar Belakang: corona virus disease (Covid-19) yang muncul di Indonesia sejak awal Maret 2020 telah menjadi ancaman serius pada semua kalangan usia, tidak  terkecuali usia remaja. Remaja merupakan usia transisi saat dimana perkembangan biologis dan psikologis terjadi. Covid-19 dapat mempengaruhi perkembangan psikologis remaja tersebut, sehingga menimbulkan kecemasan yang tidak dapat dikontrol. Salah satu faktor yang mempengaruhi kecemasan ialah pengetahuan.Tujuan: diketahui hubungan antara tingkat pengetahuan dengan tingkat kecemasan pada remaja terhadap pandemi Covid-19.Metode Penelitian: jenis penelitian deskriptif analitik dengan teknik total sampling. Responden pada penelitian ini merupakan seluruh murid kelas XII SMA Advent Balikpapan berjumlah 60 orang. Pengumpulan data menggunakan kuesioner pengetahuan yang diadopsi dari survei WHO dan kuesioner Hamilton Anxiety Rating Scale (HARS).Hasil: diketahui sebanyak 9 responden (15%) berpengetahuan cukup mengalami kecemasan ringan, sebanyak 33 responden (55%) berpengetahuan baik mengalami kecemasan ringan, sebanyak 4 responden (6,6%) berpengetahuan cukup mengalami kecemasan sedang, sebanyak 9 responden (15%) berpengetahuan baik mengalami kecemasan sedang, sebanyak 1 responden (1,7%) berpengetahuan cukup mengalami kecemasan berat, dan sebanyak 4 responden (6,7%) berpengetahuan baik mengalami kecemasan berat. Hasil analisis dengan uji chi-square didapatkan p-value yaitu 0,135 α (0,05).Kesimpulan: tidak terdapat hubungan antara tingkat pengetahuan dengan tingkat kecemasan yang dialami pada remaja, khususnya remaja kelas XII SMA Advent Balikpapan. Kata kunci : covid-19; kecemasan; pengetahuan; remaja